2001
DOI: 10.1046/j.1360-0443.2001.96228512.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective attentional bias to alcohol related stimuli in problem drinkers and non‐problem drinkers

Abstract: The present study showed it is possible to use a modified Stroop task as a measure of implicit processing of alcohol stimuli. Despite the fact that all participants were asked to ignore the words, they were unable to do so. Alcohol-related words produced more interference than neutral category words in a group of problem drinkers and a control group of high alcohol drinkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
136
0
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(160 citation statements)
references
References 46 publications
20
136
0
4
Order By: Relevance
“…First, the AD group were significantly slower at responding across all conditions compared to the non-AD group (even though this was unlikely to have been due to anxiety or depression). This delay is not unusual, and has been demonstrated in many previous studies (Cox et al, 2002;Maurage et al, 2007Maurage et al, , 2008Sharma et al, 2001).…”
Section: Resultssupporting
confidence: 77%
“…First, the AD group were significantly slower at responding across all conditions compared to the non-AD group (even though this was unlikely to have been due to anxiety or depression). This delay is not unusual, and has been demonstrated in many previous studies (Cox et al, 2002;Maurage et al, 2007Maurage et al, , 2008Sharma et al, 2001).…”
Section: Resultssupporting
confidence: 77%
“…Studies using the alcohol Stroop task did not reveal any significant differences between light and heavy drinkers (Sharma et al 2001) or between alcoholics and healthy participants (Lusher et al 2004) in terms of the number of errors made when words are related to alcohol. One reason for the absence of cognitive disinhibition in the alcohol Stroop task is that both problematic users of alcohol and healthy participants made very few errors, thus reflecting a ceiling effect.…”
Section: Introductionmentioning
confidence: 81%
“…Human drug addiction is a complex multifactorial phenomenon that features, with remarkable consistency, a difficulty in directing attention away from salient drug-related stimuli. Behavioral studies have shown that processing a nonsalient stimulus in the presence of a salient drug-related stimulus presents a significant difficulty for those dependent on cocaine (Copersino et al 2004;Hester et al 2006), alcohol (Sharma et al 2001;Ryan 2002;Cox et al 2003;Duka and Townshend 2004a, b), cannabis (Field et al 2004a), nicotine (Wertz and Sayette 2001;Powell et al 2002;Waters et al 2003;Bradley et al 2004;Field et al 2004b), or heroin (Lubman et al 2000;Franken et al 2003). Similarly, electrophysiological studies, which are able to directly quantify the allocation of processing resources to specific stimuli independently of conscious awareness, demonstrate enhanced event-related potential (ERP) responses to drugrelated stimuli compared to nonsalient stimuli across a range of addicted populations (Warren and McDonough 1999;Herrmann et al 2000Herrmann et al , 2001Franken et al 2003;van de Laar et al 2004;Lubman et al 2007b.…”
Section: Attentional Bias For Drug-related Stimulimentioning
confidence: 99%